2016
DOI: 10.1016/j.media.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging-guided attenuation correction in whole-body PET/MRI using a sorted atlas approach

Abstract: a b s t r a c tQuantitative whole-body PET/MR imaging is challenged by the lack of accurate and robust strategies for attenuation correction. In this work, a new pseudo-CT generation approach, referred to as sorted atlas pseudo-CT (SAP), is proposed for accurate extraction of bones and estimation of lung attenuation properties. This approach improves the Gaussian process regression (GPR) kernel proposed by Hofmann et al. which relies on the information provided by a co-registered atlas (CT and MRI) using a GPR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 63 publications
0
39
0
Order By: Relevance
“…Basically two categories have emerged: atlas-guided attenuation map generation approaches ( Hofmann et al, 2011 ;Bezrukov et al, 2013 ;Arabi and Zaidi, 2016a ;Marshall et al, 2013 ;Arabi and Zaidi, 2016b ) and emission-based approaches ( Rezaei et al, 2012 ;Mehranian and Zaidi, 2015 ). Atlas-guided methods primarily rely on prior information provided by registration of an atlas into target image coordinates to allow classification of bone tissues.…”
Section: E-mail Address: Habibzaidi@hcugech (H Zaidi)mentioning
confidence: 99%
See 1 more Smart Citation
“…Basically two categories have emerged: atlas-guided attenuation map generation approaches ( Hofmann et al, 2011 ;Bezrukov et al, 2013 ;Arabi and Zaidi, 2016a ;Marshall et al, 2013 ;Arabi and Zaidi, 2016b ) and emission-based approaches ( Rezaei et al, 2012 ;Mehranian and Zaidi, 2015 ). Atlas-guided methods primarily rely on prior information provided by registration of an atlas into target image coordinates to allow classification of bone tissues.…”
Section: E-mail Address: Habibzaidi@hcugech (H Zaidi)mentioning
confidence: 99%
“…Various strategies were proposed to incorporate bone tissue in PET/MRI attenuation maps in whole-body imaging ( Hofmann et al, 2011 ;Bezrukov et al, 2015 ;Ay et al, 2014 ;Arabi and Zaidi, 2016a ;Bezrukov et al, 2013 ;Marshall et al, 2013 ;Paulus et al, 2015 ). In whole-body imaging, almost all proposed methods, except joint attenuation-activity reconstruction techniques, rely on prior knowledge present in atlas images to predict bone from MRI.…”
Section: E-mail Address: Habibzaidi@hcugech (H Zaidi)mentioning
confidence: 99%
“…The study population comprised 21 patients who underwent whole-body 18 F-FDG PET/CT and MRI scanning for staging of head and neck malignancies. The study protocol was approved by the institutional ethics committee and the patients signed written informed consent.…”
Section: A Data Acquisitionmentioning
confidence: 99%
“…CT images were acquired for attenuation correction using an unenhanced low dose CT scan (120 kVp, 60 mAs, 24 × 1.5 collimation, pitch of 1.2 and 1 s/rotation) after a localization scout scan. PET data acquisition started at 146.2 ± 20 min post-injection of 18 F-FDG (371 ±23 MBq) with 3 min per bed position for a total of 4-5 beds, resulting in a total acquisition time of 15-18 min. MRI examinations were performed on the Ingenuity TF PET/MR (Philips Healthcare, Cleveland, USA) 23 using a whole-body MRI Dixon volumetric interpolated T1-weighted sequence 24 using the following parameters: flip angle 10˚, TE 1 1.1 ms, TE 2 3 voxel size, and a total acquisition time of 2-3 min.…”
Section: A Data Acquisitionmentioning
confidence: 99%
“…The study found that both atlas/machine learning methods had reduced SUV mean error in the lungs, compared with three class MRAC. However, computation time was long per target image (1100 min) owing to the multiple registrations and Gaussian process regression training …”
Section: Past and Present Attenuation Estimation Methodsmentioning
confidence: 99%